Investment management - Azian Madun; Mohd. Nizal Haniff (Oxford revision series, 2013)
The Oxford Revision Series: Investment Management summarizes the key concepts and practices of investment management which are essential to understanding this important subject. This revision book provides a succinct exposition of all the main topics of investments. It is divided into several chapters covering the workings and supervision of the financial markets as well as the types of financial assets available for investments. Topics such as modern portfolio theory, the capital asset pricing model, the efficient market hypothesis and the valuation of securities are also included to give readers a balanced and thorough understanding of the key areas in investment